'Cry God for Harry, England, and Saint George': Europe and the Limits of Integrating Identity. Issue 1 (29th January 2019) - Foster, Russell
Abstract : Since the early 1990s a dominant modernist narrative has assumed that European integration and the progressive march of secularism, multiculturalism and increased material prosperity would lead to the fading-away of tribal, national, racial and other parochial identities; identities ostensibly incompatible with a meta-national 'European' identity founded not in ethnosymbolic myth, but in cosmopolitanism. This has informed not only academic theory but has also guided 60 years of EU policy making, with Ernst Haas' doctrine of neofunctionalist spill-over dominating European assumptions that a pan-European identity would replace national affiliations. Brexit contradicts this in four ways. First, Brexit demonstrates the renewed appeal of ethnic nationalism on multiple levels: nationalist (British), sub-nationalist (English), and meta-nationalist (white nationalism). Second, Brexit demonstrates shifts in traditional nationalism in the form of gulfs in a neo-medieval society. Third, Brexit demonstrates the existence of multiple and incompatible 'European' identities. Finally, Brexit demonstrates how a specifically EUropean identity can be just as hostile and exclusionary as ethnic nationalism. This reappearance of social discord, ethnosymbolic identities, and the praxis of ethnic identity exemplified by the British, but seen across the EU, necessitates a fundamental reconsideration of the apparently irreversible trends of an unfalsifiable theory of modernist, neofunctionalist progressivism in the form of European integration. Using the British as a case study, this paper argues that the very processes of European integration have, by accelerating antagonistic national and EU identities, inadvertently constructed the apparatus for EUrope's potential disintegration.